Economic Aspects of Maritime Transport Development - Alexey Yuryevich Smirnov (North-West institute of management of the Russian Presidential Academy of National Economy and Public Administration, 2018)
In the article on the basis of the analysis of features of activity of the marine transport of Russia in 2010-2015, dynamics of its key economic indicators are defined tendencies of development of the marine transport in general and its structural components in the fast-changing environmental conditions.